2001
DOI: 10.1002/dac.503
|View full text |Cite
|
Sign up to set email alerts
|

Measurement‐based admission control for bufferless multiplexers

Abstract: In this paper we study measurement-based admission control for bufferless multiplexing, which is very attractive for real-time traffic. We first discuss a novel large deviations (LD) approach to measurement-based admission control. We then provide an extensive review of the existing literature on measurement-based admission control. We conduct simulation studies with traces of MPEG 1 encoded movies to compare the performance of the admission rules in the literature with that of our large deviations approach. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Loss estimates under bufferless fluid approximations have been used extensively in literature (e.g. [23], [24]) for analysing packet switching systems, and are justified in this case given the very small buffering (OTSIs) that core HiTSOBS nodes are likely to have. If N denotes the number of flows multiplexed at the core link, and X the overall arrival rate to the core link at a random instant of time, then X = N i=1 X i .…”
Section: A Estimating Lossmentioning
confidence: 99%
“…Loss estimates under bufferless fluid approximations have been used extensively in literature (e.g. [23], [24]) for analysing packet switching systems, and are justified in this case given the very small buffering (OTSIs) that core HiTSOBS nodes are likely to have. If N denotes the number of flows multiplexed at the core link, and X the overall arrival rate to the core link at a random instant of time, then X = N i=1 X i .…”
Section: A Estimating Lossmentioning
confidence: 99%
“…He concluded that only one algorithm among the tested algorithms, the algorithm proposed by [7], achieved acceptable results for the desired loss ratio. Breslau et al [12] used simulation to compare the performance of some of the MBAC algorithms [4,7,11,13,14]-some of these algorithms are studied by Moore as well. They found that all of the algorithms achieve nearly the same link utilization for a given packet loss rate, and that none of them are capable of accurately meeting loss targets including [7].…”
Section: Related Workmentioning
confidence: 94%
“…Moore [10] presented an implementation-based comparison of several MBAC algorithms [4,5,7,8,11]. He concluded that only one algorithm among the tested algorithms, the algorithm proposed by [7], achieved acceptable results for the desired loss ratio.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations